Alfred Flechtheim. Raubkunst und Restitution - Bambi, Andrea 1964- (Schriftenreihe der Vierteljahrshefte für Zeitgeschichte, 2015)
The tragic story of Alfred Flechtheim, his ideological defamation, and the loss of his art collection